The Power of Ethical Leadership on Good Corporate Governance and Contextual Performance - Tri Prasetiawan, Saptana; Ahmad, Irdham; Setyawati, Aswanti; Zainal, Munawaroh (Dinasti Publisher, 2025)
Contextual performance is of paramount importance within organizational settings, thereby necessitating a heightened focus on its manifestation. Therefore, this research aims to determine the influence of ethical leadership on contextual performance with good corporate governance (GCG) mediation. The sample comprised 325 employees engaged in the consumer goods, finance, trade, services, and investment sectors in Indonesia. The method of data collection employed a questionnaire utilizing a Likert scale. The analytical approach utilized structural equation modeling grounded in Partial Least Square (SEM-PLS), complemented by descriptive and correlational analyses. The findings of the research indicate that ethical leadership exerts a direct influence on both GCG and contextual performance, that GCG directly affects contextual performance, and that ethical leadership indirectly impacts contextual performance via GCG. This evidence substantiates a novel empirical framework concerning the effect of ethical leadership on employee contextual performance via GCG. This framework is posited to serve as a basis for stimulating discourse among scholars and researchers, while also acknowledging the existing limitations.